FEATURES OF CYTOKINE PROFILE IN PATIENTS WITH ATHEROSCLEROSIS - E. P. Turmova (SPb RAACI, 2014)
Our study included measuring the following biological substances: cytokines (IL-1β, IL-6, IFNγ, TNFα, IL-10, TGF-β1, TGF-β2, IL-2, IL-17); soluble receptors to cytokines (IL-2R, IL-6R, TNFαRI and TNFαRII); total serum cholesterol; indicators of intercellular matrix degradation (metalproteinases-9; tissular inhibitor of MMP-9 1 type (TIMP-1); MMP-9/TIMP 1 and MMP-9/TIMP 2 complexes) in 260 patients with clinically manifestations of coronary and lower limb atherosclerosis. Among the patients with atherosclerosis, we have found increased average levels of IL-6, TGF-β2, TNFα RI, TNFαRII, IL-2R, along with decreased IL-2 and IL-10 concentrations, increase of MMP-9/TIMP-2 ratio in blood serum. The following direct correlations were revealed between MMP-9 and IL-1β; between MMP-9/TIMP-1 complex and IL-1β, IL-2, IL-2R, IL-17, IL-10; TIMP-1 with TNFα, IL-2 and IL-2R. At high levels of the general cholesterol, an increased production of TNFα, IL-17, TGF-β1, IL-2, IL-10, MMP-9, TIMP-1 was detected, as well as decreased amounts of TNFα I and TNFαII soluble receptors in blood serum of these patients.Direct correlations were established between total blood cholesterol levels and IL-2, IFNγ, MMP- 9, TIMP-1, MMP-9/TIMP-2. However blood cholesterol levels showed reverse correlations with TNFαRI, and TNFαRII.In the course of this study, we have specified a functional imbalance between pro- and anti-inflammatory mechanisms of immune reaction in clinically expressed atherosclerosis. Significant regulatory interactions have been revealed between cytokine levels, total blood cholesterol and markers of intercellular matrix degradation.